Insistent Life Principles for Bioethics in the Jain Tradition - Donaldson, Brianne (University of California Press, 2021)
Jainism, perhaps more so than any other South Asian tradition, focuses strongly on the ethics of birth, life, and death, with regard to both humans and other living beings. Insistent Life is the first full-length interdisciplinary examination of the foundational principles of bioethics within Jain doctrine and the application of those principles in the contemporary sphere. Brianne Donaldson and Ana Bajželj analyze a diverse range of Jain texts and contemporary sources to identify Jain perspectives on bioethical issues while highlighting the complexity of their personal, professional, and public dimensions. The book also features extensive original data based on an international survey the authors conducted with Jain medical professionals in India and diaspora communities of North America, Europe, and Africa.